A measurement model of building information modelling maturity. Issue 2 (1st April 2014) - Chen, Yunfeng; Dib, Hazar; F. Cox, Robert
Abstract : Purpose: – There is a growing requirement for a rating system of building information modelling maturity (BIMM) to compare the effectiveness of modelling processes in construction projects. The literature related to BIMM contains theoretical proposals and description of their maturity models. However, the research efforts are limited and lacking substantial theoretical and empirical justifications. This paper is a unique attempt to integrate previous models by performing empirical investigations of key factors for measuring BIMM in construction projects. The paper aims to discuss these issues. Design/methodology/approach: – A national survey was designed to extract the perception of 124 BIM-related practitioners and academicians about the conceptual model. Then, exploratory and confirmatory factor analyses were employed to identify and test the key factors underlying the 27 areas. Findings: – A principal component factor analysis of the collected data had suggested a five-factor model, which explained 69.839 per cent of the variance. The construct validity of the model was further tested by confirmatory factor analysis. The results indicated that all factors were important in measuring BIMM; however, compared with the factors of technology and people, more emphasis was put on the factors of process and information. Originality/value: – The key value of the paper is to increase the understanding of multi-dimension nature of BIMM through empirical evidence and to provide practitioners and researchers with the insight regarding particular emphasis on the factors related to modelling process and information.